Pengaruh Kualitas Produk Dan Religiusitas Nasabah Terhadap Minat Pemilihan Asuransi Syariah - Siti Nurhaliza; Tasya Syasmita; Muhamad Aji Purwanto (JOURNAL OF SHARIA ECONOMICS, 2024)
Sharia insurance is increasingly in demand by the people of Indonesia, both Muslims and non-Muslims. This study aims to analyze the influence of product quality and customer religiosity on the interest in choosing sharia insurance. Data was collected through questionnaires to sharia insurance customers in Bandung City. Data analysis using multiple linear regression. The results showed that product quality and customer religiosity had a positive and significant effect on the interest in choosing sharia insurance. The better the quality of sharia insurance products and the higher the customer's religiosity, the greater the customer's interest in choosing sharia insurance. The managerial implication of this research is the need for sharia insurance companies to continue to improve the quality of their products and increase education to the public about the advantages of sharia insurance in accordance with sharia principles.